PENGARUH KAPUR DAN PUPUK KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG DI LAHAN SULFAT MASAM - LUSIANA LUSIANA; DINI ANGGOROWATI; ELLY MUSTAMIR (Jurnal Sains Pertanian Equator, 2017)
EFFECT OF LIME AND CHICKEN DUNG FERTILIZER ON THE GROWTH AND YIELD OF CORN ON ACID SULPHATE SOIL Lusiana(1), Dini Anggorowati(2), Elly Mustamir(2), Basuni,(2) (1)Student and (2)Lecturer of Agriculture Faculty Tanjungpura University Pontianak Email : lusianauntan@yahoo.com ABSTRACT   This study aims to determine the best dosage of lime and chicken dung fertilizer on the growth and yield of corn on acid sulphate soil and to investigate the interaction between lime and chicken dung fertilizer. The research conducted at Parit Canggek Village District of Sungai Kakap Kubu Raya Regency using a split plot design with two factors. The first factor is lime with two levels of treatment (1 ton/ha and 2 ton/ha), the second factor is chicken dung with 3 levels of treatment (0 ton/ha, 7,5 ton/ha and 15 ton/ha). The observed variables in this study consist of plant height, leaf area, plant dry weight, root volume, cob length, cob diameter, cob weight and weight of 1000 seeds. The results showed that the lime adding is only significant on the root volume, while the chicken dung fertilizer significantly affected all the observed variables, but no interaction between the lime addition and chicken dung fertilizer. In this study, additoin of the dose of lime 1-2 ton/ha and chicken dung fertilizer 7,5-15 ton/ha can increase growth and yield of cord in acid sulphate soil. The addition of chicken dung 7,5 ton/ha dosage for root volume and plant height on fourth week. The addition of chicken dung 15 ton/ha for the dry weight, leaf area and plant height on second, third and fifth week, while the effective dosage results for cob length, cob diameter and weight of 1000 seeds is 15 ton/ha of chicken dung, but for the cob weight is 7,5 ton/ha. The addition of lime 1 ton/ha for plant height on second, third and fifth week, while on generative growth the effective dose for cob diameter is 2 ton/ha of lime dosage and for 1000 grain weight, cob length and cob weight per plot is 1 ton/ha of lime dosage.   Keywords: acid sulphate soil, chicken dung, corn, lime